Understanding inter-individual variability in purpose in life: Longitudinal findings from the VA Normative Aging Study - Hill, Patrick L. (Psychol Aging, 2015)
Research has demonstrated the importance of having a purpose in older adulthood; however, little is known about whether and how individuals vary on sense of purpose over time. The current study examined patterns of mean- and individual-level change in purpose among men in the Veterans Affairs Normative Aging Study (n = 587; M(age) = 74 years) across a three-year span. Findings demonstrate that while little mean-level change was present, there was inter-individual variability in change. Further research is needed to understand why these changes occur, as age, health status, and personality failed to predict individual fluctuations in purpose.